Travaux du cercle linguistique de Prague n.s. = Prague Linguistic Circle papers. Volume 1 - Hajičová, Eva (Travaux du Cercle linguistique de Prague ;, 1995)
This volume is the first one of the revived series of Travaux, which was the well-known international book series of the classical Prague Linguistic Circle, published in the years 1929-39. The tradition of the Circle still attracts attention in broad circles of European and American linguistics. The first volume of the new series is divided into five sections: 1. Introductory papers characterizing the development of the Prague School in the recent decades; 2. Methodological issues of structural and functional linguistics; 3. Sentence structure; 4. Discourse patterns; 5. Theory of litera.